The Economics of Colonialism: Hunger, Expropriation and Mendicancy in Mohammed Dib's Algerian Trilogy - Benjamin J Sparks (Studies in 20th & 21st Century Literature, 2016)
The colonial endeavor as argued by Aimé Césaire in his Discourse on Colonialism is neither an evangelization, nor a philanthropic enterprise, nor an aid system to combat systems of ignorance, sickness, and tyranny (32). It is a system of power relations based on exploitation and violence without concern for the Other. To borrow Césaire’s term, colonialism is nothing other than chosification; it makes objects of people, tearing them from their land, home, and families, depriving them of essential, life-providing commodities. Colonization’s social and economic policies disrupted traditional society and the Algerian way of life more so than the physical military conquests had done. Albert Camus, as a Pied-Noir author, provides an outsider’s perspective on the suffering of the Algerian population, declaring, “Pour aujourd’hui, j’arrête ici cette promenade à travers la souffrance et la faim d’un peuple. On aura senti du moins que la misère ici n’est pas une formule ni un thème de méditation. Elle est. Elle crie et elle désespère. Encore une fois, qu’avons-nous fait pour elle et avons-nous le droit de nous détourner d’elle ?” (Camus 40) ‘For now, I must end this survey of the suffering and hunger of an entire population. The reader will have seen, at least, that misery here is not just a word or a theme for meditation. It exists. It cries out in desperation. What have we done about it, and do we have the right to avert our eyes.’ Mohammed Dib’s Algerian trilogy gives flesh to Camus’s statement; misery in these novels shouts and despairs, it shows itself through the characters and narration. This literature shows, as only literature can, the Algerians’ misery, and their desperation; it creates a collective trauma to be shared and understood by many through the act of storytelling. This collective trauma brings out the emotions of the characters and allows the reader to feel empathy toward the plight of the Algerians.
Keywords: economics; colonialism; Mohammed Dib; hunger; expropriation; mendicancy